2014
DOI: 10.1055/s-0034-1368444
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of In Vitro Absorption, Distribution, Metabolism, and Excretion (ADME) Properties of Mitragynine, 7-Hydroxymitragynine, and Mitraphylline

Abstract: Mitragyna speciosa (kratom) is a popular herb in Southeast Asia, which is traditionally used to treat withdrawal symptoms associated with opiate addiction. Mitragynine, 7-hydroxymitragynine, and mitraphylline are reported to be the central nervous system active alkaloids which bind to the opiate receptors. Mitraphylline is also present in the bark of Uncaria tomentosa (cat's claw). Several therapeutic properties have been reported for these compounds but limited information is available on the absorption and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 26 publications
4
64
2
3
Order By: Relevance
“…Mitragynine seemed to be a weaker inhibitor than verapamil, although it is remarkable that both P app values, A to B and B to A, were reduced. These findings are in line with recent findings [14] that not only mitragynine, but also 7-hydroxymitragynine, a further alkaloid in Mitragyna speciosa (Kratom), were inhibitors of P-gp. Only diclofensine did not influence the apparent permeabilities and the ER of R123.…”
Section: Caco-2 Transport Of Structurally Diverse Doasupporting
confidence: 92%
See 1 more Smart Citation
“…Mitragynine seemed to be a weaker inhibitor than verapamil, although it is remarkable that both P app values, A to B and B to A, were reduced. These findings are in line with recent findings [14] that not only mitragynine, but also 7-hydroxymitragynine, a further alkaloid in Mitragyna speciosa (Kratom), were inhibitors of P-gp. Only diclofensine did not influence the apparent permeabilities and the ER of R123.…”
Section: Caco-2 Transport Of Structurally Diverse Doasupporting
confidence: 92%
“…P-gp [11][12][13][14][15][16]. However, this is an issue of growing interest, particularly because appearance and abuse have increased dramatically over the last years [17][18][19][20].…”
mentioning
confidence: 99%
“…We found that MG was two times more BBB permeable than 7‐OHMG, which is in agreement with previous study that reported MG permeability to be between 1.45 and 1.50 times higher than 7‐OHMG, measured in epithelial cell models (Manda et al . ). The higher rate of BBB permeation of MG could partly be related to its lipophilicity, estimated log P oct of 4.11 (ACD ChemSketch), higher than that estimated for 7‐OHMG, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…In one report, mitragynine was shown to have CYP1A2 induction activity (Lim et al, ). In addition, P‐gp inhibitory activity of mitragynine and 7‐hydroxymitragynine was recently reported by us (Manda et al, ) and later by others (Meyer et al, ). To our knowledge, there are no reports on the effects of M. speciosa extract or its alkaloids on the transcriptional activity of PXR.…”
Section: Introductionmentioning
confidence: 99%